FORGOTTEN POST OPERATIVE NASAL SPLINT & ORO-NASAL FISTULA - Sheikh, Nadeem Ahmed; Nadeem, Kanwal (Journal of Ayub Medical College Abbottabad, 2018)
Oro-nasal fistula is an anomalous communication between the floor of nasal passage and the roof of the oral cavity. It may develop as a congenital defect e.g. cleft palate, or rarely, consequent to an operative procedure like a sub muco-perichondrial resection surgery of the nasal septum. After nasal septal corrective surgery, follow up of the patient with meticulous nasal toilet and detailed examination is mandatory. In operated patients who do not report to follow up, and later on present with persisting nasal discharge, pain, nasal blockage and exsanguination must alert a clinician for any evidence of a possibly retained foreign object. Inadvertently retained nasal splints can cause long lasting morbidity due to a possible chronic sinusitis, toxic shock syndrome and palatal perforation. Keywords: Nasal septum; nasal lavage; nasal septal perforation; epistaxis; nasal surgical procedures; splints, fistula